Teacher Education and Leadership for Change: Exploring Faculty Perspectives - Castle, Joyce B. (Alberta Journal of Educational Research, 2001)
Given the call for newer forms of leadership in schools, teacher educators have a central role to play in promoting, modeling, and critiquing leadership for change. This study explored the thinking of a group of teacher educators in one Canadian context to gain some insight into their views of educational leadership and the extent to which these promote or constrain leadership for change. Findings revealed some diversity in faculty views about leadership, but also illustrated that traditional views remain deeply embedded in teacher educators' thinking.